2010
DOI: 10.1111/j.1472-4642.2010.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence of Chilean long-tailed snake (Philodryas chamissonis) across latitudes: conservation threats for different lineages

Abstract: Artículo de publicación ISIAim The Chilean long-tailed snake (Philodryas chamissonis) has a wide distribution across different latitudes and ecosystems in Chile ranging from the south of the Atacama Desert (26 S) to the extremely humid Valdivian temperate rain forest (40 S). Throughout this vast distribution, which is isolated by the Andes mountain range on the east and the Pacific Ocean on the west, there are biogeographical boundaries and large geographical barriers that must have played an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 35 publications
5
25
0
1
Order By: Relevance
“…Cytogenetic and molecular studies of the lizard L. monticola also showed a high level of genetic variation in this watershed, where the Maipo River would have acted as a geographic barrier, producing divergence between populations located on opposite banks (Lamborot and Eaton 1997;Torres-Pérez et al 2007). This result also concurs with the results of Sallaberry-Pincheira et al (2011) in the Figure 3 Geneland analysis with posterior probability isoclines which indicate extensions of the genetic groups found (I, II, III; see Figure 2B). Black dots indicate locations of the 23 analyzed localities; thick black lines indicate the geographic border of Chile.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Cytogenetic and molecular studies of the lizard L. monticola also showed a high level of genetic variation in this watershed, where the Maipo River would have acted as a geographic barrier, producing divergence between populations located on opposite banks (Lamborot and Eaton 1997;Torres-Pérez et al 2007). This result also concurs with the results of Sallaberry-Pincheira et al (2011) in the Figure 3 Geneland analysis with posterior probability isoclines which indicate extensions of the genetic groups found (I, II, III; see Figure 2B). Black dots indicate locations of the 23 analyzed localities; thick black lines indicate the geographic border of Chile.…”
Section: Discussionsupporting
confidence: 81%
“…Those authors identified the topography of the central Chile and oceanic barriers as the most important factors which limited the connectivity of populations among river basins. Finally, in a genetic study of populations of the colubrid Philodryas chamissonis from 29°to 38°S, Sallaberry-Pincheira et al (2011) found a high level of phylogeographic structure, four latitudinally differentiated haplogroups, and high levels of intrapopulational genetic diversity in the Maipo River basin (33°S).…”
Section: Introductionmentioning
confidence: 99%
“…The differentiation between northern and southern populations has also been reported in the king cobra (O. hannah) using phylogenetic analyses of ND2 and CR (Suntrarachun, Chanhome, & Sumontha, 2014), and other amphibian and reptile species (Inger & Voris, 2001). Population phylogenetic studies of other snake species, such as D. acutus (Huang et al, 2007), A. laevis (Lukoschek et al, 2008), P. chamissonis (Sallaberry-Pincheira et al, 2011), Gloydius brevicaudus (Ding, Gan, He, & Zhao, 2011), Vipera latastei/monticola group (Velo-Antón et al, 2012) and N. atra (Lin et al, 2014(Lin et al, , 2012, showed similar results to those of this study in finding that, for example, geography, climate, and/or distance correlate with regional genetic variation.…”
Section: T a B L E 2 Degrees Of Phi (φ)-mentioning
confidence: 73%
“…A study by Sallaberry-Pincheira et al (2011) provides an example of how phylogeography can aid in the delineation of ESUs. This study sought to determine whether geographic boundaries throughout the range of the Chilean long-tailed snake ( Philodryas chamissonis) have led to significant genetic divergence among isolated populations.…”
Section: Phylogenetics and Phylogeographymentioning
confidence: 99%